The Existence Of Traditional Games In Pontianak City Schools and Communities - Triansyah, Andika; Suci Lukitowati; Fitriana Puspa Hidasari (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
This study aims to describe the existence of folk games and traditional sports in Pontianak City. Folk games are symbolic of hereditary knowledge that has many functions, not only as part of the culture of folk games, but can develop character, basic movements and mental emotional conditions of children. The research method used in this study is descriptive quantitative in the form of a survey to find out how much knowledge students have. The subjects in the study were students in the city of Pontianak totaling 311 students. With a distribution of 118 students in elementary schools, 91 students in junior high schools, and 102 students in senior high schools. In addition, to obtain information from the community, it was carried out to the Komite Permainan Rakyat and Olahraga Tradisional (KPOTI) Kalimantan Barat. There are 12 games that are known to students in the city of Pontianak, including tapok pipit, bentengan, ketapel, gala hadang, buah lima, lompat tali, taba, gasing, main jengkal-jengkalan, egrang, sumpit and gonde. The intensity of students playing traditional games in the frequent category is 37% and the rare and very rare category is at 63%. Furthermore, students most often play traditional games during holidays, which is 58%, and play traditional games at school by 23% and are played in the afternoon and evening by 19%. There are 7 obstacles in playing, the biggest obstacle is the absence of friends to play with a percentage of 67%, the second biggest obstacle is that there are no game tools with a percentage of 47%, then fear of getting hurt 21%, not knowing how to play 16%, often fighting 10%, prohibited parents 5%, and unpleasant 4%. In general, traditional games in the city of Pontianak, especially among children, are still often played both during free time and during school breaks.